Beyond power transition theory: explaining the absence of U.S.-China power shift in the Middle East - Zhao, Yueting (Frontiers in Political Science, 2025)
The paper examines the power dynamics between China and the United States in the Middle East, arguing that there is no power transition in the region. First, the balance of power between these two countries in the region remains unchanged despite the decreasing involvement of the United States and the growing presence of China. Second, major regional leaders are steadily increasing their presence and trying to govern the region by themselves. Third, satisfied with the existing governing framework in the Middle East at the dyadic level, China has no desire to augment its engagement and replace the U.S. in the region. The incongruity between China’s ideological frameworks and its progressively assertive approach to foreign policy further hinders its potential to emerge as a regional leader.